ECHOCARDIOGRAPHIC ASSESSMENT OF HYPERTENSIVE CHANGES IN ELDERLY PATIENTS OF ISOLATED SYSTOLIC HYPERTENSION WITH SPECIAL REFERENCE TO CARDIOVASCULAR COMPLICATIONS - BIJAYA KUMAR BEHERA; BEHERA, BIJAYA KUMAR; MOHANTY, RAKESH; JENA, SUKANTA KUMAR; BEHERA, SUSANTA SEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to assess the echocardiographic changes and cardiovascular complications in patients with isolated systolic hypertension (ISH). Methods: This was an observational cross-sectional study done in the Departments of General Medicine, Cardiology, and Radiodiagnosis of MKCG Medical College and Hospital, Berhampur, Odisha, India. Seventy patients above the age of 65 years with systolic blood pressure (BP) ≥140 mm Hg and diastolic BP <90 mm Hg, without any secondary causes of hypertension and antihypertensive drug therapy were selected for this study. Echocardiography and electrocardiography studies were implemented for demonstrating the development of cardiovascular complications. Results: Of 70 cases (41 males and 29 females), 64.3% were asymptomatic and 35.7% were symptomatic, with palpitation being the major symptom, 40% (28 cases) developed retinopathy, 45.71% developed increased left ventricular mass index (p=0.04), 18.57% had increased in LV volume (>90 ml/m2), 30% cases had regional wall motion abnormalities, 27.1% had reduced ejection fraction (<56%), and 52.66% showed LA enlargement in this study (p=0.048). Doppler measurements of diastolic filling were significant in patients with ISH with higher peak atrial velocity (A wave) of 79.71±11.79 cm/s and a lower ratio of peak early to atrial velocity of 0.82±0.29. Conclusion: This study demonstrates that elderly patients with ISH had a prevalence of concentric left ventricular hypertrophy (LVH) which was found to be more in female patients than in male patients followed by left atrial enlargement.